Influence of sleep duration and quality on depression symptoms among nurses during the Omicron outbreak: a cross-sectional survey - Yingying Gu; Pinglang Hu; Caijun Dai; Shuhong Ni; Qiqi Huang (BMC Nursing)
Abstract Background Nurses who work during the global pandemic are known to experience physical and psychological exhaustion, as well as severe anxiety and depression symptoms. This study aimed to explore the relationships between sleep duration, sleep quality, and depression symptoms among nurses during the outbreak of the Omicron variant. Methods A cross-sectional study was conducted between August 2022 and September 2022. Participants (N = 2140) were evaluated for depression symptoms via the Hospital Anxiety and Depression Scale (HADS), and sleep was evaluated via the Pittsburgh Sleep Quality Index (PSQI), and "short sleep duration" was defined as ≤ 5 h per day. Demographic information was also collected. Binary and multivariate logistic regression was performed to assess the relationships between sleep duration, sleep quality, and depression symptoms. Results In total, 2140 nurses were included in this study; 1481 (69.2%) had poor sleep quality, while 866 (40.4%) had depression symptom scores > 7 according to the HADS criteria. Both duration and quality of sleep were significantly correlated with depression symptoms among nurses (P < 0.001). In multivariable analyses adjusted for potential confounders, short sleep duration (≤ 5 h) was associated with an odds ratio (OR) of 2.26 (95% confidence interval [CI] 1.25–4.07), whereas poorer sleep quality was associated with an OR of 1.97 (95% CI 1.32–2.94) for experiencing depression symptoms. Conclusions Following the COVID-19 pandemic, there was a strong association between the sleep quality, sleep duration and depression symptoms among nurses. We recommend the development of targeted interventions to increase sleep duration, enhance sleep quality and alleviate depression symptoms.